Various configurations and transition strategies of nanostructure induced bistable disks. (15th March 2019) - Yi, Shenghui; He, Xiaoqiao; Lu, Jian
Highlights: Bistable metallic disks are manufactured by nanostructuring disks in a localized region. Refined analytical models characterizing bistable behaviors are proposed. Six transition types are found for bistable disks with different nanostructured regions. Bistable metallic disks have good stabilities indicated by snapping forces. Abstract: In contrast to conventional bistable disks manufactured using soft materials in spherical or domelike configurations, new bistable disks with designable configurations and high load-bearing capacities are proposed and developed based on the nanotechnology of surface mechanical attrition treatment (SMAT). A simple analytical model with explicit results, refined analytical models and numerical models are formulated to predict two stable configurations and study their transition processes. A simple algorithm that includes a confined equation for the formulated Ritz models is developed via a displacement control strategy to capture the full snapping processes of the bistable disks, which are actuated by a point force. The analytical models for the bistable disks identify various stable configurations and six transition strategies, and these are discussed systematically with respect to the design parameters. The ratio of the nanostructured region in the disks is found to have a critical influence on the stable configurations and the transition processes. The results from the experimentally manufactured bistable disks validate the obtained theoretical results.